Improving Students’ Creative Problem-Solving Skills in Online-Onsite Based Mathematics Learning - Tetty Natalia Sipayung; Imelda Imelda; Tatag Yuli Eko Siswono; Masriyah Masriyah (STAI Hubbulwathan Duri, 2022)
Learning during the COVID-19 period is a concern in the world of education. This is because the learning system has changed from the previous one and it has not been used by both students and teachers. In response to this, it is necessary to conduct action research using the Kemmis and McTaggart models on online-onsite mathematics learning, namely boldly through online platforms and the request of students. The subjects of this study were seventh-grade junior high school students who found 27 people. In contrast, the object of this research is to increase students’ creative problem-solving skills and increase teacher activity and student behaviour. Through the instruments used in online-onsite based learning, the results show that there is an increase in the percentage of classical learning completeness in creative problem-solving abilities of students who pass the minimum KKM in the 1st cycle from the percentage of initial ability results but have not shown achievement. While the results of observations of student behaviour and teacher activities meet the criteria achieved. Therefore, it is continued to cycle II by correcting the weakness in cycle I. The implementation of cycle II shows that all performance indicators have been achieved. Through these results, of course, it is a consideration that in improving problem-solving skills, it is recommended to do online-onsite based learning, especially in mathematics.